Palm Oil Clinker as Drainage Layer in Green Roof System under Malaysia Climatic Conditions - Khairul Anuar, Shahid; Mohd Arif, Sulaiman; Norhaiza, Ghazali; Wafty, Abdul Rahman; Azhani, Zukri (2013)
Green roof has become common in most of developed countries in Europe. It has many benefits in term of storm water management, urban heat island mitigation, and thermal performance thus leads to energy conservation. However, the green roof system is still based on the conventional materials which use expanded clay, expanded shale or pumice as drainage layer. Being among of the largest producer of palm oil in the world, Malaysia produces palm oil clinker as a waste material in the process of extracting the oil. The palm oil clinker has a potential of replacing the conventional materials for the green roof system. The fine aggregates produced from clinker are lightweight,porous and irregular in shape and thus having low values of bulk density and specific gravity. This paper emphasizes on the potential of using palm oil clinker as drainage layer in green roof system as replacement of conventional materials (expanded clay, expanded shale, pumice, etc.). The ability for draining of palm oil clinker is studied since the purpose of drainage layer is to drain the excess water and to ensure aeration of substrate layer and root. This study used an experimental procedure in which hydraulic conductivity, infiltration rate and bulk density was measured. Besides, the plant developments of selected green roof plants were also monitored to see any effect from the palm oil clinker replacement by means of experimental trays to simulate the real green roof system. It was found that palm oil clinker has a good ability of draining the excess water and there is no effect in term of plant development when the palm oil clinker is used as drainage layer.